Strategi Pengembangan Usaha dalam Meningkatkan Okupansi - Wulandari Rahmadhani; Sepria Susanti (Lembaga Yasin AlSys, 2026)
Business development strategies to increase occupancy in the hotel industry have received attention in various studies; however, research that specifically discusses the formulation of business development strategies for Sharia-based resorts through the Strengths, Weaknesses, Opportunities, and Threats (SWOT) approach remains limited. This study aims to analyze the business development strategy of Kamang Resort & Convention in increasing occupancy through the identification of internal and external factors that influence business sustainability. This study used a qualitative approach with a case study design, involving eight informants selected through purposive sampling. Data were collected through observation, in-depth interviews, and documentation, and were then analyzed using SWOT analysis by identifying strengths, weaknesses, opportunities, and threats as the basis for formulating business development strategies. The results show that Kamang Resort & Convention has strengths in the form of natural scenery, adequate facilities, a strategic location, and experienced human resources. However, business management still faces weaknesses in the form of a limited number of employees, suboptimal marketing, and limitations in certain facilities. Business development opportunities come from the use of information technology, cooperation with travel agents, and word-of-mouth promotion, whereas threats include digital fraud practices, economic conditions, and weather factors. These findings contribute to the application of SWOT analysis in hotel business management and expand understanding of occupancy improvement strategies in Sharia-based resorts. The conclusion of this study emphasizes the importance of optimizing internal strengths and utilizing external opportunities as the basis for sustainable business development. The implications of this study can serve as a reference for the management of Kamang Resort & Convention in improving competitiveness, marketing effectiveness, and service quality.